2020
DOI: 10.29309/tpmj/2020.27.05.4149
|View full text |Cite
|
Sign up to set email alerts
|

Awareness among health care professionals regarding nosocomial pathogens and role of fomites in their transmission.

Abstract: Objectives: This study was performed to access the knowledge of health care professionals regarding health care associated infections, nosocomial pathogens, fomites and their role in transmission of nosocomial pathogens. Study Design: Descriptive, questionnaire based, cross-sectional study. Setting: Tertiary care hospital of Lahore, Punjab. Period: From October 2017 to January 2018. Material & Methods: Questionnaires were carefully formulated to access basic knowledge of physicians, surgeons and nurses. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Thus, theCenter for Disease Control and Prevention (CDC) developed guidelines for Infection Prevention and Control (IPC) standard precautions practices ashand hygiene, Personal Protective Equipment (PPE), sharps safety, safe injection practice, and respiratory hygiene / cough etiquette (16) . Inadequate knowledge and practice of IPC precautions contributes to an increase in HAIs (6,17,18) . Despite the CDC guidelines issueda decade ago, various studies have been conducted and reported inadequate levels of knowledge and practices regarding IPC precautions.For instance, inadequate levels of knowledge and practice towards IPC precautions were reported among nurses in various studies, one conducted in Palestinian Hospitals (19) , another study in Eastern Nigeria (20) , another study in Iran (21) , another study in Yemen (22) , another study in Ethiopia (23) , and another study regarding compliance with IPC standard precautions in Brazil and Hong Kong (24) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, theCenter for Disease Control and Prevention (CDC) developed guidelines for Infection Prevention and Control (IPC) standard precautions practices ashand hygiene, Personal Protective Equipment (PPE), sharps safety, safe injection practice, and respiratory hygiene / cough etiquette (16) . Inadequate knowledge and practice of IPC precautions contributes to an increase in HAIs (6,17,18) . Despite the CDC guidelines issueda decade ago, various studies have been conducted and reported inadequate levels of knowledge and practices regarding IPC precautions.For instance, inadequate levels of knowledge and practice towards IPC precautions were reported among nurses in various studies, one conducted in Palestinian Hospitals (19) , another study in Eastern Nigeria (20) , another study in Iran (21) , another study in Yemen (22) , another study in Ethiopia (23) , and another study regarding compliance with IPC standard precautions in Brazil and Hong Kong (24) .…”
Section: Introductionmentioning
confidence: 99%